Social media influencers effectiveness among millennials and generation Z in Malaysia: a conceptual framework - Laily Najwa Yapp; Emily Yapp Hon Tshin; Zurina Patrick (Universal Publishers, 2024)
Purpose: Digitalization, sensory stimulation, societal scepticism, and personalised experiences are decreasing traditional advertising's effectiveness. SMIs are widely used by marketers to promote their products and businesses. It is unclear how social media users pick influencer loyalty. Social media influencer authenticity is measured to promote emotional loyalty. Design/methodology/approach: This quantitative survey will assess Malaysian social media influencers' brand endorsement effectiveness. 108 Millennials (Gen Y) and Generation Z who have social media profiles and follow at least one influencer will be surveyed. Findings: The expected outcome is this study is that all of social media influencers’ determinants has positively correlated with emotional attachment and emotional attachment also has positive. Research limitations/implications: The first limitation is that hypothesized model was tested is too general way of determinants of influencers without any context. Next limitation is that the focus of research is conducted in Malaysia. Practical implications: This research will assist social media influencer marketers to choose trustworthy influencers and be emotionally attached to the brand supported. It will also help brand managers reduce the uncertainty of advertising. Originality/value: This study examines how social media influencers' credibility affects Millennials and Gen Z's emotional relationships. Previous research examined trustworthiness, sociability, and understandability. attachment and research is to link influencer-follower emotional attachment and loyalty using variables from various articles.